A rare case of recurrent breast malignant phyllodes tumor with lung, axillary and mediastinal lymph nodes metastasis - Hashim, Mohd Azren; Sarif, Mat Salleh; Che Alhadi, Shahidah; Ahmad Affandi, Khairunisa (Asian Journal of Case Reports in Surgery, 2021)
Background: Phyllodes tumour (PT) is very rare fibroepithelial tumor of the breast and divided based on the World Health Organization into benign, borderline, and malignant subtypes. The most common type of phyllodes tumor is benign, however malignant phyllodes tumors have important clinical implications, as they are more likely to recur locally and potentially metastasize. The most common sites of distant metastasis include the lung, bone, and liver. Case Presentation: A 34-year-old female presented with right nipple blood discharge with palpable right breast lump. Tru-cut biopsy showed atypical cell and subsequently she underwent right wide local excision and histopathological examination showed malignant phyllodes tumor. She then presented again with recurrent ulcerated right breast lump. Repeated tru-cut biopsy showed atypical cell for which she underwent simple mastectomy with final diagnosis of malignant phyllodes tumor. Two weeks after surgery, she presented with right axillary mass with anterior right chest wall mass. Further evaluation demonstrated that masses over right axillary, right anterior mediastinal and bilateral lungs suggestive of metastasis. Conclusion: We presented a rare case of aggressive malignant phyllodes tumor with recurrent and distant metastasis to bilateral lungs, axillary and mediastinal lymph nodes.